Use of augmented reality technology at the stages of the life cycle of a capital construction facility - S. I. Evtushenko; M. D. Kuzenko (Vestnik MGSU)
Introduction. The application of information modelling (BIM) and augmented reality (AR) technologies at the stage of construction and subsequent operation of capital construction facilities (CCF) is analyzed.Materials and methods. Potential possibilities of optimization of work of installation and construction teams or carrying out of project expertise using information modelling (BIM) technologies are shown. Due to the application of this technology: the terms of installation works at the construction site are reduced (as a result, costs are reduced and labour efficiency is increased); the terms of the project expertise are reduced (at the stage of construction object commissioning). The main idea is to combine BIM technology at the construction stage and augmented reality technology. Combination of these technologies will make it easier to identify deviations from the project and reduce the labour intensity of installation works.Results. The proposed information tables for visualization of elements of the information model of the construction object and the key principles of their filling with data on the example of a pipeline on the basis of given points of the constructed three-dimensional model are of great importance for the construction practice. Examples of AR application at the operation stage on the example of a water meter and an electric meter are considered.Conclusions. Types and content of information visualization tables of the main pipeline are formulated and determined on the basis of which the construction of a three-dimensional model of the pipeline at the construction stage of the facility is carried out. An example of the content of the information table of visualization of individual elements of the information model of the construction object at the operational stage is given on the example of a water and electric meter. The directions of further research are given.